2000
DOI: 10.1097/00007890-200004150-00017
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Preservation of Isolated Rat Skeletal Muscles Stored for 16 Hours at 4??c1

Abstract: The results showed that the addition of BDM and antioxidants (trolox and deferione) to the bathing solutions improved the preservation of the function, metabolism, and cytoarchitecture of isolated skeletal muscles after cold storage for 16 hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The primary reason for developing the hamster RET free flap model was that both contractile muscle [17] and microcirculatory measurements [15] can be used to evaluate the efficacy of preservation techniques in future studies. For example, the potential for recovery of muscle function after cold ischemia depends on recovery of both the parenchymal (muscle) cells and their vascular supply [16,29] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary reason for developing the hamster RET free flap model was that both contractile muscle [17] and microcirculatory measurements [15] can be used to evaluate the efficacy of preservation techniques in future studies. For example, the potential for recovery of muscle function after cold ischemia depends on recovery of both the parenchymal (muscle) cells and their vascular supply [16,29] .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that interventions that lead to re-establishment of local vasodilator signals will contribute to prevention of hypoperfusion and the no-reflow phenomenon. Interventions that could be employed in future research include cold preservation and several pharmacological approaches [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of highly reactive species appears to be triggered by a cold-induced increase in the cellular chelatable (or 'free'), 'redox-active' iron pool [Rauen et al, 1999Huang and Salahudeen, 2002;Rauen and de Groot, 2004], and mitochondria have been shown to be the major target of the reactive species (see 'ATP' below) Rauen et al, 2003;Salahudeen et al, 2003]. A similar mechanism also appears to be at play during cold storage of muscle tissue [Magni et al, 1994;van der Heijden et al, 2000]. To stop this iron-dependent injury, the strong, hexadentate but poorly membranepermeable iron chelator deferoxamine and the smaller, aromatic and thus more lipophilic membrane-permeable iron chelator LK 614 are present in TiProtec and its variants used in this study.…”
Section: Main Injurious Mechanisms and Counterbalancing Ingredients Omentioning
confidence: 99%
“…Especially human muscle tissue is regularly dissected in operation theaters, which are located far away from the respective diagnostic or research laboratory. Accordingly, there is an urgent need to optimize transport conditions as an impaired membrane potential [Oredsson et al, 1993] and decreased response to electrophysiological stimuli [van der Heijden et al, 2000] with subsequent loss of function and structural integrity of specimens were detected after shortterm cold storage [van der Heijden et al, 2000;Wagh et al, 2000]. So far, only few studies have been published in which muscle biopsies showed promising results regarding (ultra)structural alterations after 1-5 days when stored in a new tissue medium [Sandberg et al, 2007].…”
mentioning
confidence: 99%